The Creeds of A.D. 325 Antioch, Caesarea, Nicaea - Pollard, T. Evan (Scottish journal of theology, 1960)
The Letter of the Synod of Antioch contained in a Syriac MS. of the eighth or ninth century (Codex Parisinus Syriacus 62), to which Edward Schwartz first drew attention in 1905, has thrown light on the period immediately preceding the Council of Nicaea and on the proceedings of the Council itself. After much initial controversy, mainly between Schwartz and von Harnack, this document is now generally accepted as authentic.The Synod of Antioch, of which nothing was hitherto known, appears to have assembled in order to settle the difficulties which had arisen in the Church at Antioch after the death of Bishop Philogonius (ca. A.D. 322), one of three Bishops whom Arius described as ‘unlearned heretics’; Eustathius, Bishop of Beroea, was appointed to fill the vacancy. The Synod was attended by at least fifty-nine bishops from Syria and Palestine, forty-nine of whom also attended the Council of Nicaea a few months later.